Choice of alloy composition and thermal treatment conditions of internal-combustion engines valve seats - O. S. Komarov; G. G. Makaeva; D. O. Komarov (Литьë и металлургия, 2000)
The experience on alloys development for grind the valve seat of internal combustion engine is generalized in this paper. The findings of an influence of chemical composition and heat treatment condition of the castings for grind the valve seats on their wear resistance and machinability are presented.